2021
DOI: 10.1063/9.0000108
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer studies on magnetism in FeSe

Abstract: Iron selenide (FeSe) was used to investigate magnetic properties by using Mössbauer spectroscopy. The crystalline structure of the sample was found to be tetragonal and hexagonal with a 3c structure. The temperature-dependent magnetic susceptibility curve under 100 Oe confirmed the spin rotation temperature TS = 150 K. Based on the applied field dependent magnetization measurements up to 15 kOe at 295 K, the saturation magnetization and coercivity were found to be 8.03 emu/g and 357.40 Oe, respectively. The sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…As displayed in Figure b, the 57 Fe Mössbauer spectrum of FeSe-NS can be fitted into two sextets (Fe site 1 and Fe site 2) and a typical doublet (Fe site 3). Combining the isomer shift data in Table S2, it can be seen that all Fe sites of FeSe-NS are Fe 2+ , where Fe site 1 and Fe site 2 demonstrate antiferromagnetism and Fe site 3 has paramagnetism. , Hence, FeSe-NS exhibits intrinsic antiferromagnetism at 300 K (Figure c).…”
Section: Synthesis Physical Properties and Electrochemistrymentioning
confidence: 93%
See 1 more Smart Citation
“…As displayed in Figure b, the 57 Fe Mössbauer spectrum of FeSe-NS can be fitted into two sextets (Fe site 1 and Fe site 2) and a typical doublet (Fe site 3). Combining the isomer shift data in Table S2, it can be seen that all Fe sites of FeSe-NS are Fe 2+ , where Fe site 1 and Fe site 2 demonstrate antiferromagnetism and Fe site 3 has paramagnetism. , Hence, FeSe-NS exhibits intrinsic antiferromagnetism at 300 K (Figure c).…”
Section: Synthesis Physical Properties and Electrochemistrymentioning
confidence: 93%
“…Combining the isomer shift data in Table S2, it can be seen that all Fe sites of FeSe-NS are Fe 2+ , where Fe site 1 and Fe site 2 demonstrate antiferromagnetism and Fe site 3 has paramagnetism. 32,33 Hence, FeSe-NS exhibits intrinsic antiferromagnetism at 300 K (Figure 2c).…”
mentioning
confidence: 96%
“…This appears to be a reliable physical picture for several reasons. First, the applied experimental temperature range is below the Debye temperature of pyrite (Schönbrunn crystal as 610, [ 3 ] 568 ± 20, [ 45 ] and 640 ± 5 K [ 46 ] ). Second, when the PDOS of the FeS 2 is inspected, the number of the PDOS at ω0/3 is much lower.…”
Section: Calibration Curve and Raman Mode Phonon Scatteringmentioning
confidence: 99%
“…The separation process of pyrite is mainly based on flotation, mineral flotation is based on the difference in hydrophilicity of the mineral surface to achieve the separation of different minerals [3, 4], commonly used in the flotation of pyrite collector xanthate, dithiophosphate, and so on [5, 6], of which xanthate is the most important and most widely used collector in pyrite flotation [3, 7–9]. Therefore, in recent years, the mechanism of the action of xanthate on the mineral surface has received the attention of many researchers, mainly through Fourier transform infrared spectroscopy (FTIR) [8], x‐ray photoelectron spectroscopy (XPS) [1], secondary ion mass spectrometry (SIMS), x‐ray diffraction (XRD) [10], microcalorimetry [11], and other physicochemical means, and the majority of them believe that a single xanthate and pyrite metal xanthates and double xanthates are formed after interaction and the products are co‐adsorbed on the pyrite surface [12, 13]. However, with the development of quantum theory, the theoretical study of density functional theory (DFT) as a new method applied to the flotation process found that the action of reagents on the mineral surface is not only simple interactions between ions [9, 14, 15], but mainly the coordination between reagents and the mineral surface [1, 7, 11, 16].…”
Section: Introductionmentioning
confidence: 99%